2003
DOI: 10.1002/bjs.4101
|View full text |Cite
|
Sign up to set email alerts
|

Temporary closure of open abdominal wounds by the modified sandwich–vacuum pack technique

Abstract: The modified sandwich-vacuum pack technique of temporary abdominal wall closure is easy and rapid, cost effective and provides an effective means of containing abdominal wall contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 8 publications
1
73
1
11
Order By: Relevance
“…18,19 Fistulas are attributed to desiccation and erosion of the bowel wall, possibly as a result of adhesions with the underlying dressing. 20 Rao et al 12 reported a 20% incidence of fistula development in their series of patients with open abdomens treated with negative pressure therapy; of these patients 66% eventually died. They recommended caution in the use of negative pressure dressings, particularly where a bowel anastomosis has been performed or enterotomies have been closed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…18,19 Fistulas are attributed to desiccation and erosion of the bowel wall, possibly as a result of adhesions with the underlying dressing. 20 Rao et al 12 reported a 20% incidence of fistula development in their series of patients with open abdomens treated with negative pressure therapy; of these patients 66% eventually died. They recommended caution in the use of negative pressure dressings, particularly where a bowel anastomosis has been performed or enterotomies have been closed.…”
Section: Discussionmentioning
confidence: 98%
“…18 Various methods for managing laparostomies have been described. 6,19,20 Many of these are difficult to apply and somewhat cumbersome to manage. There is a requirement for a temporary closure device that is not only simple to apply, but also actively removes wound and visceral exudates, promotes tissue granulation, minimises complications, and provides mechanical containment of abdominal contents.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbable meshes have little tensile strength and can result in evisceration during patient turning with the non-absorbables being associated with a moderate rate of intestinal fistula. 196,197 The further advantages of the VAC proprietary devices over temporary mesh usage include their versatility to the contour of large defects permitting the utilization of a laterally placed stoma in conjunction 198 and potential use even in the presence of a pre-existing intestinal fistula. 199 Where possible, stomas should be avoided as the geography of the abdominal wall may change in such a way that they retract significantly or where in a delayed setting they can compromise abdominal wall reconstruction and rectus advancements.…”
Section: Surgical Decompressionmentioning
confidence: 99%
“…The absorbable meshes have little tensile strength and can result in evisceration during patient turning with the non-absorbables being associated with a moderate rate of intestinal fistula. 196,197 The further advantages of the VAC proprietary devices over temporary mesh usage include their versatility to the contour of large defects permitting the utilization of a laterally placed stoma in conjunction 198 and potential use even in the presence of a pre-existing intestinal fistula.…”
mentioning
confidence: 99%
“…51 A 3-l plastic irrigation bag is sutured to the wound edges and continuous high-pressure suction applied to achieve temporary abdominal wall closure. This is the so-called laparostomy (Fig.…”
Section: Contaminated Woundsmentioning
confidence: 99%